2020
DOI: 10.30909/vol.03.02.205226
|View full text |Cite
|
Sign up to set email alerts
|

Fireside tales: understanding experiences of previous eruptions and factors influencing the decision to evacuate from activity of Volcán de Fuego

Abstract: Volcán de Fuego (Guatemala) is an active stratovolcano capable of large (VEI~ě2) explosive eruptions like that of 3 rd June 2018, which triggered pyroclastic flows that devastated the community of San Miguel Los Lotes and caused hundreds of fatalities and severe long-term socioeconomic impacts. Future volcanic risk mitigation efforts are likely to involve temporary evacuation of local communities, the success of which requires cooperation between locals, scientists, and decision-makers. However, locals' experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Our findings suggest that the most meaningful area of improvement for future eruption communications both in Hawai ' i and other volcanically active regions include 1) making official eruption information easier for residents to access and interpret and 2) continuing to strengthen the trust and credibility of official sources/messengers of this information among the impacted communities. These lessons, which apply most readily to the LERZ due to the high proportion of negative perceptions from LERZ participants regarding HVO's eruption communications, are consistent with those provided by Williams et al [2020] [Haynes et al 2008;Donovan et al 2014;Naismith et al 2020].…”
Section: Lessons For Future Eruption Hazard Communicationssupporting
confidence: 66%
See 1 more Smart Citation
“…Our findings suggest that the most meaningful area of improvement for future eruption communications both in Hawai ' i and other volcanically active regions include 1) making official eruption information easier for residents to access and interpret and 2) continuing to strengthen the trust and credibility of official sources/messengers of this information among the impacted communities. These lessons, which apply most readily to the LERZ due to the high proportion of negative perceptions from LERZ participants regarding HVO's eruption communications, are consistent with those provided by Williams et al [2020] [Haynes et al 2008;Donovan et al 2014;Naismith et al 2020].…”
Section: Lessons For Future Eruption Hazard Communicationssupporting
confidence: 66%
“…Covello [2003] stated that successful crisis communication includes using "clear, non-technical language appropriate to the target audience," and Sellnow et al [2009] described the importance of effectively tailoring one's messages to fit the needs of a particular group or population. McBride [2017] found that official earthquake preparedness documents in Christchurch, New Zealand, did not effectively prepare residents for the 2010-2011 Canterbury Sequence due to containing "overly long, jargon-laden text," while vulnerable populations living on active volcanoes in Indonesia or Ecuador have been most resilient to hazards from these volcanoes when they have access to the relevant scientific information [Mei et al 2013;Few et al 2017;Naismith et al 2020]. In fact, local people's trust in scientists at Tungurahua Volcano, Ecuador, has resulted from the direct, sustained interactions (i.e.…”
Section: Trusted and Effective Sources/messengers Of Hazard Informationmentioning
confidence: 99%
“…However, the series of PDCs in Barranca Las Lajas extended over 12 km from the summit, longer than all the other flows, and buried the town of San Miguel Los Lotes (Figure 1d), killing several hundreds of people. Official numbers report 332 people missing as a result of the eruption, although the death toll could be as high as 2,900 people (Naismith et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pyroclastic Density Currents (PDCs) are the most hazardous direct consequence of explosive volcanism. They are estimated to be responsible for 28.1% of the casualties of volcanic eruptions documented between 1500 AD and 2017 (Brown et al, 2017) with the last disaster to date being the 3 June 2018 Volcàn Fuego (Guatemala) PDCs that killed between 332 and 2,900 people (Naismith et al, 2020). PDCs can be produced by a wide spectrum of processes from transient mechanisms such as gravitational collapse of a lava dome or of an eruptive column to long-lived sustained mechanisms such as pyroclastic fountaining (Branney and Kokelaar, 2002;Sulpizio et al, 2014;Lube et al, 2020).…”
Section: Introductionmentioning
confidence: 99%